Mycorrhizae: Sustainable Agriculture and Forestry - Siddiqui, Zaki Anwar; Akhtar, Mohammad Sayeed; Futai, Kazuyoshi (Springer Netherlands : Imprint: Springer, 2008)
Mycorrhizal fungi are microbial engines which improve plant vigor and soil quality. They play a crucial role in plant nutrient uptake, water relations, ecosystem establishment, plant diversity, and the productivity of plants. Scientific research involves multidisciplinary approaches to understand the adaptation of mycorrhizae to the rhizosphere, mechanism of root colonization, effect on plant physiology and growth, biofertilization, plant resistance and biocontrol of plant pathogens. This book discusses and goes into detail on a number of topics: the molecular basis of nutrient exchange between arbuscular mycorrhizal (AM) fungi and host plants; the role of AM fungi in disease protection, alleviation of soil stresses and increasing grain production; interactions of AM fungi and beneficial saprophytic mycoflora in terms of plant growth promotion; the role of AM fungi in the restoration of native ecosystems; indirect contributions of AM fungi and soil aggregation to plant growth and mycorrhizosphere effect of multitrophic interaction; the mechanisms by which mycorrhizas change a disturbed ecosystem into productive land; the importance of reinstallation of mycorrhizal systems in the rhizosphere is emphasized and their impact on landscape regeneration, and in bioremediation of contaminated soils; Ectomycorrhizae (ECM) and their importance in forest ecosystems and associations of ECM in tropical rain forests function to maintain tropical monodominance; in vitro mycorrhization of micro-propagated plants, and visualizing and quantifying endorhizal fungi; the use of mycorrhizae, mainly AM and ECM, for sustainable agriculture and forestry.